1997
DOI: 10.1111/j.1440-1630.1997.tb00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural issues from practice

Abstract: This paper addresses cultural issues in occupational therapy practice through a review of the occupational therapy and culture literature and a brief exploration of key issues highlighted in analyses of discussions and critical incidents in transcripts of interviews with 86 occupational therapists. The data, collected in conjunction with the Intercultural Interaction Project, highlights seven important categories of issues from the perspective of therapists: (i) professional values; (ii) family roles and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…Service providers reported an improved capacity to engage and involve families from different cultural and language backgrounds through use of the FGST. Communication and language have been found to be critically important cultural issues in occupational therapy practice (Fitzgerald et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service providers reported an improved capacity to engage and involve families from different cultural and language backgrounds through use of the FGST. Communication and language have been found to be critically important cultural issues in occupational therapy practice (Fitzgerald et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Service providers reported an improved capacity to engage and involve families from different cultural and language backgrounds through use of the FGST. Communication and language have been found to be critically important cultural issues in occupational therapy practice (Fitzgerald et al 1997). They identified that one of the most important features of intercultural communication was developing a means of articulating and reconciling these differences, in a satisfying way for all involved.…”
Section: Discussionmentioning
confidence: 99%
“…Culture is reflected in its products: the learned, shared beliefs, values, attitudes and behaviours that are characteristic of a society or population. Culture is not a static phenomenon; it is dynamic and ever changing, but it maintains a sense of coherence (Fitzgerald, Mullavey‐O’Byrne & Clemson, 1997, p. 3).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The inability of occupational therapists to clearly formulate their professional identity and role is worrisome. Even more so when one considers that the ability to make explicit the very fundaments of one's profession can strengthen professional identity (1), and, as a result, facilitate a client-centred approach (22), contribute to improved inter-professional collaboration (1,3), and develop a more effective practice both ethically (1,18) and culturally (23,24).…”
Section: Introductionmentioning
confidence: 98%